Reducing soil erosion in cassava production systems in Thailand: A farmer participatory approach - Vongkasem, Wilawan; Klakhaeng, Kaival I.; Hemvijit, Somnuek; Tongglum, Anuchit; Katong, Sompong; Suparhan, Danai; Howeler, Reinhardt H. (International Center for Tropical Agriculture, 2001)
The project on Cassava Production System Adjustment to Reduce Soil Erosion is a cooperative project among the Department of Agricultural Extension (DOAE), Department of Agricultural (DOA) and the Centro Internacional de Agricultura Tropical (CIAT). The purpose of the project is to make farmers aware of the importance of soil erosion and to develop and disseminate suitable and effective measures to reduce the problem. This is done by the use of a farmer participatory approach, in which farmers are asked to select and test in their own fields cassava production practices that reduce soil erosion. The first phase of the project had a duration of five years (1994-1998) and was implemented in two pilot sites in Nakhon Ratchasima and Sra Kaew provinces. The results of the project indicate that once farmers saw the amounts of soil loss in their own erosion control trials, they realized the importance of erosion and the need to control soil degradation in cassava areas. They also tested, evaluated and selected suitable methods for reducing soil erosion. The farmers in the two pilot sites selected mainly the use of vetiver grass contour barriers as the most effective and suitable technique. They now grow vetiver grass for this purpose on about 48 hectares, while the planting of vetiver grass is still expanding. The method of participatory research involves farmers directly in decision making at every step, from planning the project to obtaining results and drawing conclusions, and lets farmers select the treatments to be tried by themselves. This encourages them to learn how to analyze problems and find solutions collectively that are in line with the needs of the community as a whole. The method of implementing this project is considered to be efficient for the development and transfer of new technologies to farmers and rural communities, in order to enhance the adoption of more sustainable and more productive agronomic practices.